Althusser, Foucault, and the Subject of Civility - Toby Miller (Studies in 20th & 21st Century Literature, 1994)
This paper seeks to paint a picture of how discernible links between Althusser and Foucault can assist us to theorise the life of cultural subjects inside established and emergent liberal-capitalist states. Althusser's querying of a humanistic foundation to political philosophy and the social contract is connected to Foucault's contention that modernity invented the subject as a centre of inquiry and that centre became the site constructing obedient citizens.
Keywords: Althusser; Foucault; civility; liberal-capitalist states; humanism; political philosophy; social contract; modernity; citizenry